فاعلية برنامج إرشادي وفق منظور الزمن لتحسين الأمن النفسي لدى المراهق المتمدرس - الأرقط، عائشة, منصر، فاطمة (جامعة الوادي university of Eloued, 2020)
ملخص: هدفت هذه الدراسة إلى معرفة فاعلية برنامج إرشادي قائم على منظور الزمن لتحسين الأمن النفسي لدى المراهق المتمدرس كما هدفت إلى معرفة الفروق في القياسين القبلي والبعدي للمجموعة التجريبية على مقياس الأمن النفسي بعد تطبيق البرنامج الإرشادي وكذا معرفة الفروق في القياس البعدي بين المجموعتين التجريبية والضابطة, والكشف عن الفروق بين الجنسين والفروق في الشعبة الدراسية في القياس البعدي للمجموعة التجريبية. استخدمت الدراسة الحالية المنهج التجريبي ذو التصميم المجموعات المتكافئة، المجموعة التجريبية والمجموعة الضابطة وقياسين قبلي وبعدي للمجموعتين على عينة قوامها (20) تلميذ وتلميذة تم توزيعهم بشكل عشوائي على المجموعتين، حيث طبق البرنامج الإرشادي القائم على منظور الزمن على المجموعة التجريبية وهذا بعد تحديد الحاجات الإرشادية عن طريق المقابلة الفردية من أجل تطبيق البرنامج الإرشادي, ومقياس الأمن النفسي لزينب شقير (2005). وبغية التحقق من فرضيات الدراسة الحالية تم الاعتماد الرزمة الإحصائية للعلوم الاجتماعية (SPSS) النسخة (22) باستخدام مجموعة من الأساليب الإحصائية منها اختبار (ت) T.TEST لحساب الفروق. وأسفرت نتائج الدراسة على ما يلي: - توجد فروق ذات دلالة احصائية بين متوسط درجات المجموعة التجريبية في القياس القبلي والقياس البعدي بعد تطبيق البرنامج الإرشادي على مقياس الأمن النفسي لصالح القياس البعدي. - توجد فروق ذات دلالة احصائية بين متوسط درجات المجموعة التجريبية والمجموعة الضابطة في القياس البعدي بعد تطبيق البرنامج الإرشادي على مقياس الأمن النفسي لصالح المجموعة التجريبية. - لا توجد فروق ذات دلالة احصائية بين الجنسين (ذكور، إناث) للمجموعة التجريبية في القياس البعدي بعد تطبيق البرنامج الإرشادي على مقياس الأمن النفسي. - توجد فروق ذات دلالة احصائية بين الشعبة الدراسية (علمي، أدبي) للمجموعة التجريبية في القياس البعدي بعد تطبيق البرنامج الإرشادي على مقياس الأمن النفسي لصالح العلمين. Abstract: This study aimed to know the effectiveness of a time-based mentoring program to improve psychological security in the adolescent school, as well as to identify the differences in the tribal and dimension standards of the experimental group on the psychological security scale after the application of the extension program, as well as to identify the differences in dimensional measurement between the experimental and control groups, and to detect gender differences and differences in the study division in the dimension measurement of the experimental group. The current study used the pilot method with the design of equal groups, the experimental group and the control group and two tribal and post-group measurements on a sample of (20) pupils randomly distributed to the two groups, where the time perspective-based guidance program was applied to the experimental group and this after determining the guidance needs through the individual interview in order to apply the guidance program, and the psychological security measure of Zainab Choucair (2005). In order to verify the current study hypotheses, the Statistical Package of Social Sciences (SPSS) version (22) was adopted using a range of statistical methods, including T.TEST to calculate differences. The results of the study resulted in: - There are statistically significant differences between the average grades of the experimental group in tribal and dimensional measurement after the application of the indicative program on the psychological security measure in favor of dimensional measurement. - There are statistically significant differences between the average grades of the experimental group and the control group in the dimension measurement after the application of the indicative program on the psychological security scale for the experimental group. There are no statistically significant differences between the sexes (male, female) of the experimental group in dimensional measurement after the application of the indicative programme on the psychological security scale. - There are statistically significant differences between the study division (scientific, literary) of the experimental group in dimensional measurement after the application of the indicative program on the psychological security scale in favor of the two scientists.
دراسة ميدانية لدى عينة من تلاميذ الأولى ثانوي بمتقنة الشهيد شعباني عباس بالدبيلة الوادي
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: منظور الزمن، الأمن النفسي، الارشاد النفسي; Perspective temporelle, sécurité psychologique, conseil psychologique; Time perspective, psychological security, psychological counseling